An overview of Early Paleozoic arc systems in New Brunswick, Canada, and eastern Maine, USA - Fyffe, Leslie R.; van Staal, Cees R.; Wilson, Reginal A.; Johnson, Susan C. (Atlantic Geoscience, 2023)
A plate tectonic model involving northwesterly retreat of an Iapetan subducting slab has been developed over the last three decades to explain the time span of volcanism recorded within the development of Early Paleozoic arc systems preserved in New Brunswick. These arc systems are referred as the Penobscot arc-backarc (514–482 Ma), and Popelogan–Meductic arc (478–460 Ma). Opening of the Tetagouche backarc basin associated with the Popelogan–Meductic arc was diachronous and heterogeneous and involved volcanism associated mainly with the crustal extension and rifting between 472–455 Ma. The complex evolution of the Tetagouche backarc basin is examined in respect to six sub-basins, containing relatively well documented stratigraphic sections in New Brunswick: namely from northeast to southwest the Fournier, California Lake, Bathurst, Sheephouse Brook, Napadogan, and Becaguimec sub-basins. Recently, alternate plate tectonic models have been proposed for the northern Appalachians based on newly acquired geochronological data from northern Maine. We integrate these new data with existing stratigraphic, structural, paleontological, and geochemical evidence to support and refine the previously proposed migrating-arc model for New Brunswick and Maine.